Effects of Monetary Reward on Employee Performance: A Case Study of Kahondo Education SACCO. - Akorebirungi, Joshua (Kabale University, 2024)
The study examined the factors contributing to the persistent poor performance of employees in microfinance institutions. It focused on the rewards and incentives utilized by Kahondo SACCO, the impact of salaries and wages on employee performance, and the role of bonuses in enhancing performance. The research employed a descriptive design to gather information after incidents had occurred, incorporating qualitative methods such as interviews. Data was collected through questionnaires and interview guides, using simple random and purposive sampling techniques. Both qualitative and quantitative methods were used to analyze data from a sample size of 30 respondents. The findings revealed that Kahondo Education Sacco used various rewards, including monetary incentives, non-monetary opportunities, employee recognition, and benefits in kind. It was found that quality is a crucial long-term business strategy, and motivating employees leads to higher performance. The need for satisfaction and achievement through skilled and autonomous work was emphasized. Salaries and wages were identified as significant motivators for effective performance, with effective performance appraisal systems creating a motivated and committed workforce. The study also highlighted that discretionary bonuses, profit-sharing bonuses, year-end bonuses, and other forms of bonuses motivate employees, attract joint investments, and form part of employee recognition and rewards programs. The study recommended that SACCOs should consistently provide rewards such as monetary and financial rewards, employee recognition, non-monetary opportunities, and employee assistance programs to improve morale and motivation, ultimately enhancing performance.